2019
DOI: 10.29328/journal.cjog.1001017
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia induced acute pancreatitis in pregnancy: Learning experiences and challenges of a Case report

Abstract: Hyperglyceridemia induced pancreatitis in pregnancy accounts for 4% of all cases of acute pancreatitis. Though rare, hypertriglyceridemia induced pancreatitis may lead to fatal maternal and fetal complications, even maternal death. Its management during pregnancy remains a challenge for many physicians. Management options are limited in pregnancy. In the refractory cases, management options and timing of delivery is debatable. Here we report a case of hyperglyceridemia induced pancreatitis and the challenges f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Lipid levels in the first trimester are usually the same as pre-pregnancy and change significantly in the second and third trimesters [ 29 ]. There is usually a two to four-fold increase in plasma triglyceride level during pregnancy [ 30 ], which is normally well-tolerated (< 300 mg/dL or 3.3 mmol/L) and does not affect the mother or fetus [ 31 ], but in some high-risk women, triglyceride level may increase to an abnormally high level (more than 95 th centile for the age) or even severe level (> 1000 mg/dL or 11.3 mmol/L) [ 32 ]. Moreover, previous studies demonstrated that women from East and South Asia, including China, have higher levels of TG, TC and LDL than western populations [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid levels in the first trimester are usually the same as pre-pregnancy and change significantly in the second and third trimesters [ 29 ]. There is usually a two to four-fold increase in plasma triglyceride level during pregnancy [ 30 ], which is normally well-tolerated (< 300 mg/dL or 3.3 mmol/L) and does not affect the mother or fetus [ 31 ], but in some high-risk women, triglyceride level may increase to an abnormally high level (more than 95 th centile for the age) or even severe level (> 1000 mg/dL or 11.3 mmol/L) [ 32 ]. Moreover, previous studies demonstrated that women from East and South Asia, including China, have higher levels of TG, TC and LDL than western populations [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Timely treatment of patients who are found to have gallstones can help prevent APIP. Patients with hyperlipidemia should stop taking lipid-lowering drugs during pregnancy owing to the lack of definitive evidence of their safety during pregnancy [ 32 ]. However, they should be fully informed of the possible complications and treatment methods during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia (HL) AP in pregnancy has been reported to be associated with a maternal mortality rate of ~20% (6). HLAP can cause serious complications, such as fetal distress, intrauterine death, maternal multiple organ failure, abdominal compartment syndrome and pancreatic encephalopathy, when not treated in a timely manner (7).…”
Section: Treatment and Diagnosis Of Hyperlipidemia Acute Pancreatitis...mentioning
confidence: 99%